2021
DOI: 10.1080/0020739x.2021.1977402
|View full text |Cite
|
Sign up to set email alerts
|

The role of generating questions in mathematical modeling

Abstract: This study aims to clarify the role of generating questions in mathematical modeling and construct principles for teaching and learning mathematical modeling with an emphasis on generating questions. To achieve this purpose, the role of generating questions was determined by solving a sprinkler problem and considering the investigation process. Generating questions requires noticing the unknown and cognitive steps to elucidate the unknown and solve the problem. The process and outcome of generating questions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…These problems involve specific criteria and can be interpreted in various ways, such as modelling problems, application problems, and contextualized problems (Brown, 2019;McGrane, 2020). Therefore, the teacher and preservice teacher must be able to solve and pose the real-world mathematical problems (also known as the modelling problem), which is a necessary tool to enhance students' mathematical learning in the present and future (Blum, 2015;Sevinc & Lesh, 2018;Fukushima, 2021;Brady, Ramírez, & Lesh, 2024). Although the preservice teachers' abilities to pose meaningful problems were impacted by the students' own abilities, research has shown that preservice teachers encountered difficulties when attempting to combine mathematical modeling and problem posing in the classroom, particularly when starting with real-world contexts.…”
Section: Introductionmentioning
confidence: 99%
“…These problems involve specific criteria and can be interpreted in various ways, such as modelling problems, application problems, and contextualized problems (Brown, 2019;McGrane, 2020). Therefore, the teacher and preservice teacher must be able to solve and pose the real-world mathematical problems (also known as the modelling problem), which is a necessary tool to enhance students' mathematical learning in the present and future (Blum, 2015;Sevinc & Lesh, 2018;Fukushima, 2021;Brady, Ramírez, & Lesh, 2024). Although the preservice teachers' abilities to pose meaningful problems were impacted by the students' own abilities, research has shown that preservice teachers encountered difficulties when attempting to combine mathematical modeling and problem posing in the classroom, particularly when starting with real-world contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Embora diferentes pesquisas sobre a MM, na perspectiva da Educação Matemática, apontem para dificuldades reveladas por alunos e professores em sala de aula, em particular, no estudo de problemas sobre contextos reais como encaminham Sodré e Guerra (2018), Sodré (2019) e Fukushima (2021), a literatura da área (Borromeo Ferri, 2006;Blum & Borromeo Ferri, 2009, Perrenet & Zwaneveld, 2012, Blum, 2015, Greefrath & Vorhölter, 2016, Vorhölter et al, 2019, Barquero & Jessen, 2020 propõe o uso do ciclo de MM como uma ferramenta didática para minimizar parte da complexidade provedora de dificuldades para alunos e professores.…”
Section: Introdução E Justificativa Do Problema De Investigaçãounclassified